2019
DOI: 10.3390/s19071740
|View full text |Cite
|
Sign up to set email alerts
|

Feasible Classified Models for Parkinson Disease from 99mTc-TRODAT-1 SPECT Imaging

Abstract: The neuroimaging techniques such as dopaminergic imaging using Single Photon Emission Computed Tomography (SPECT) with 99mTc-TRODAT-1 have been employed to detect the stages of Parkinson’s disease (PD). In this retrospective study, a total of 202 99mTc-TRODAT-1 SPECT imaging were collected. All of the PD patient cases were separated into mild (HYS Stage 1 to Stage 3) and severe (HYS Stage 4 and Stage 5) PD, according to the Hoehn and Yahr Scale (HYS) standard. A three-dimensional method was used to estimate si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…The number of patients in stages I to V was 22, 27, 53, 87, and 7, respectively. More details on the exclusion criteria, imaging instrument, and experimental design can be found in Hsu et al. 21 This clinical study was approved by the Medical Ethics Committee of E-Da Hospital. All patients signed written informed consent before participating.…”
Section: Methodsmentioning
confidence: 99%
“…The number of patients in stages I to V was 22, 27, 53, 87, and 7, respectively. More details on the exclusion criteria, imaging instrument, and experimental design can be found in Hsu et al. 21 This clinical study was approved by the Medical Ethics Committee of E-Da Hospital. All patients signed written informed consent before participating.…”
Section: Methodsmentioning
confidence: 99%
“…Next, 6 well-known classification methods, which are support vector machine (SVM), naive Bayes (NB), random forests (RF), XGboost (XGB), logistic regression (LR), and linear discriminant analysis (LDA), are used to learn classifiers for PD imaging classification with the above 6 sets of features separately [ 3 , 9 , 23 , 24 , 25 ]. The comparison study is conducted under the following repeated hold-out with 100 rounds of 5-fold cross-validation (CV) and stratified sampling scheme.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Prashanth et al [ 8 ] proposed to draw ‘indirect 3D features’ by building a regression surface of an ROI based on the 2D-combined image. Hsu et al [ 9 ] found that the classification performance for identifying PD is improved by calculating the volumes of an ROI in 3D space. Cheng et al [ 10 ] adopted the 3D features such as volume, surface area, and diameter to describe the geometric characteristics of the volumes of interest to assist the diagnosis of idiopathic PD.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations